Insécurité routière des jeunes piétons - Thierry Brenac (Territoire en Mouvement, 2008)
This investigation is aimed at better understanding accident processes involving injuries among young pedestrians and at examining the possible preventive strategies. It is based on a qualitative analysis of detailed accident data (complete police reports) concerning young pedestrian injuries and on an analysis of the scientific literature related to the influence of public space design and planning, social and psychological environment, or dealing with the effects of preventive measures. Results show that the most part of young pedestrian accident processes can be described by six main accident scenarios. Various strategies for preventing such accidents are then discussed.